Transforming primary school teachers’ perceptions of the ‘place’ of teaching reading: the role of Reading to Learn methodology - Mgqwashu, Emmanuel Mfanafuthi; Makhathini, Bheka (The IIE, 2017)
This paper reports on the interventionist study on the role that Rose’s (2005) Reading to Learn methodology plays in transforming primary school teachers’ perceptions of the role of explicit teaching of reading for educational success. Located within the qualitative case study design, the study used semi-structured interviews and the reading literacy intervention called Reading to Learn methodology to generate data. The study was conducted in grades 3 and 6 classrooms in a rural primary school in KwaZulu-Natal province, South Africa, and the research site and study participants were selected purposively. Research findings reveal that the Reading to Learn methodology has the potential to undo classroom practices that favour the elite and marginalise the majority, and transform teachers’ perceptions of the ‘place’ of teaching reading explicitly within formal education. With sufficient exposure to this pedagogy, learners across class lines have the opportunity to experience education for all, epistemological access, and education for success.
Keywords: Reading and comprehension; Education for success; Linguistics